MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL MATERI KERAGAMAN SUKU BANGSA DAN BUDAYA MELALUI BIMBINGAN BELAJAR KELOMPOK PADA SISWA KELAS IVB SD NEGERI 01 SURUH KECAMATAN TASIKMADU KARANGANYAR SEMESTER II TAHUN 2014/2015 - Dewi R, Hariyanti (Widya Wacana: Jurnal Ilmiah, 2015)
The problem of this research is â€œCan study group guidance improve the study result ofSocial Studies of the fourth grade students in SDN 01 Suruh Tasikmadu Karanganyar semester IIin the academic year of 2014/2015â€The purpose of this research is to improve the study result of Social Studies through studygroup guidance method with the material is ethnic group and cultura variety to the fourth gradestudents in SDN 01 Suruh Tasikmadu Karangnayr semester II in the academic year of 2014/2015.The kind of this research is Classroom Action Reseacrh with the subject the fourth gradestudents in SDN 01 Suruh Tasikmadu Karanganyar semester II in the academic year of2014/2015. This grade consists of 34 students, this research was carried out for about 3 months,from February until April 2015. This research includes 3 cycles. The data collecting method inthis research is test and documentation. Meanwhile, the data analysis technique is qualitativedescriptive technique for 3 cycles.The result of this research concludes that study group guidance can improve the studyresult of Social Studies of the fourth grade students in SDN 01 Suruh Tasikmadu Karanganyarsemester II in the academic year of 2014/2015. It can be seen from the score of study result ofsocial studies in the pre and post research that improve in every cycle as well as the indikatordetermined. In the pre research, the score average score is 64, cycle 1 is 68, 72 in cycle II, and82 in cycle 3.Key words: Study group guidance, Study result, Social Studies